The effect of hypnotherapy methods on understanding and readiness on swimming learning in higher education - Syahrastani, Syahrastani (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This research was conducted because understanding and readiness for swimming learning are still problematic. Hypnotherapy methods are assumed to be the factors that influence the understanding and readiness of swimming learning of students in higher education. This study aims to determine the effect of using hypnotherapy methods on the understanding and readiness of swimming lessons in higher education. This research uses the quantitative correlation method. The population is 150 students who take swimming lessons in higher education, and a sample of 50 students who were selected using purposive random sampling. The questionnaire is an effective data collection method to test the variables to be measured and the answers expected by the respondents. The questionnaire applies a Likert scale by providing an opportunity to answer each item. Data were analyzed using regression analysis. The results showed that (1) there was an increase in students' understanding of swimming lessons using hypnotherapy methods, (2) there was an increase in student readiness in swimming lessons using hypnotherapy methods.